Radiation refrigeration building enclosure material based on flattened bamboo board and preparation method of radiation refrigeration building enclosure material

By performing high-pressure delignification treatment and mechanical compression on flattened bamboo boards, combined with UiO-66 spraying technology, the problem of difficulty in recycling and degradation of existing radiation refrigeration materials is solved, and efficient refrigeration and durability of bamboo-based building enclosure materials are achieved.

CN119820677APending Publication Date: 2025-04-15CENTRAL SOUTH UNIVERSITY OF FORESTRY AND TECHNOLOGY
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202510006955.6
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-01-03
Publication Date
2025-04-15

AI Technical Summary

Technical Problem

Existing radiation refrigeration materials are difficult to recycle and naturally degrade, and there are problems such as poor mechanical properties.

Method used

By delignifying the flattened bamboo plates in an autoclave with alkali liquid and peroxy acid in a high pressure reactor, a porous and fluffy bamboo plate is formed, and the denseness and hydrophobic properties of the bamboo plates are improved by mechanical compression and UiO-66 spraying.

Benefits of technology

The radiation refrigeration performance and durability of bamboo-based building enclosure materials are achieved, and the material has good mechanical properties and environmentally friendly degradability.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119820677A_ABST
    Figure CN119820677A_ABST
Patent Text Reader

Abstract

The invention provides a radiation refrigeration building enclosure material based on flattened bamboo boards and a preparation method of the radiation refrigeration building enclosure material, and belongs to the technical field of bamboo board materials. The method comprises the following steps: partially removing lignin in a flattened bamboo board by using an alkaline reagent to obtain a partially delignified bamboo board with a porous fluffy cell wall structure, and completely removing residual lignin by using peroxy acid to obtain a white completely delignified bamboo board, and then a super-strong bamboo plate with a compact structure and excellent mechanical property is obtained through mechanical cold pressing treatment, a metal organic framework material UiO-66 is adopted for spraying the surface of the super-strong bamboo plate, and the novel bamboo-based building enclosure material with the radiation refrigeration performance is obtained. The preparation process is simple, the cost is low, and the prepared novel radiation refrigeration building enclosure material can be recycled or degraded and is a green and environment-friendly radiation refrigeration material.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of bamboo board materials, and in particular to a radiant cooling building enclosure material based on flattened bamboo boards and a preparation method thereof. Background Art

[0002] Construction, industry and transportation are the three areas with the largest energy consumption in the world. Among them, building energy consumption accounts for 33% of the total social energy consumption, and building cooling energy consumption accounts for 15% of the total human energy consumption. The development of energy-saving, emission-reducing and green environmentally friendly cooling technology has become a research hotspot. Radiative cooling is a technology that achieves cooling by radiating its own energy. Its mechanism is based on the characteristics of thermal radiation. By controlling the surface ultrastructure, chemical composition and other parameters of the material, the thermal radiation emitted from the surface can be selectively absorbed or escaped. When the thermal radiation energy escaping from the surface is greater than the absorbed energy, the structure can achieve a cooling effect. This process does not require energy consumption and has no gas emissions. It is a new type of green passive cooling method that can effectively reduce building energy consumption.

[0003] The seven-layer alternating photonic crystal structure material developed by Shanhui Fan's research group at Stanford University in 2014 can reflect 97% of sunlight, and has an average emissivity of 65% in the atmospheric window band. It also achieved radiative cooling of about 5°C below the ambient temperature during the day for the first time, but the manufacturing cost of the photonic crystal is high. In 2017, Professor Ronggui Yang's research group at the University of Colorado used scalable roll-to-roll technology to manufacture silica-polytetramethylpentene film, in which silica microspheres were embedded in the polymer and 200nm thick metallic silver was plated on the back as a reflective layer using electron beam evaporation. Spectral test analysis shows that the film has a reflectivity of 0.96 in the 0.3-2.5μm band, an average emissivity greater than 0.93 in the 8-13μm band, and an average radiative cooling power of 93W / m at noon (11:00-14:00) under direct sunlight. 2 However, this method uses synthetic polymers as matrix materials, which are difficult to degrade naturally at the end of their life cycle and are prone to environmental pollution. In 2019, the research group of Professor Liangbing Hu at the University of Maryland, USA, used wood as raw material for the first time, and prepared wood-based passive radiation cooling materials by a two-step method of chemical delignification and mechanical hot pressing. This cooling wood can reflect 96% of sunlight, and its average emissivity in the atmospheric window band is greater than 90%. It can achieve a cooling of more than 4°C during the day. It can save 20-60% of energy when used directly in house construction. It also has good mechanical strength and biodegradability. It is a new green building material that can be widely used in desert areas.

[0004] Bamboo is a widely distributed fast-growing herb with a structure, organization and chemical composition similar to wood. The cell wall contains 40%-50% cellulose, 14%-25% hemicellulose and 16%-34% lignin. Among them, cellulose has the highest degree of polymerization, which can reach about 10,000. It has a stable crystal structure and is difficult to dissolve in acid, alkali and other solutions. Hemicellulose has a degree of polymerization of about 60-200 and is an amorphous polymer. It is easily degraded in aqueous, acidic and alkaline solutions under heating or high temperature conditions. Lignin is a phenolic structural compound, an amorphous disordered structure with a light absorption effect, which will affect the refrigeration effect of bamboo. Lignin molecules contain active groups such as phenolic hydroxyl, alcoholic hydroxyl and aromatic groups, which can be removed by alkalization, acid hydrolysis, sulfonation and oxidation using alkali solution, acid solution, sulfonate solution and peroxyacid solution. A large number of microporous structures are formed inside the delignified bamboo board. The disordered photon structure strongly scatters sunlight, which can reduce the bamboo board's absorption of sunlight, making it have great development potential in the field of refrigeration technology. However, the fully delignified bamboo board also has problems such as easy water absorption and swelling, poor mechanical properties, and easy yellowing under light that need to be solved.

[0005] Metal organic framework materials (MOFs) are crystalline materials with ultra-high surface area and porous structure, which are self-assembled by inorganic metal ions as nodes and carboxylic acid or nitrogen-containing organic matter as multi-dentate ligands. In 2008, the Cavka research group of the University of Oslo in Norway first reported a rigid zirconium 1,4-carboxybenzene MOF (MOF-UiO-66) with Zr as the metal center and terephthalic acid as the organic ligand. The test results showed that UiO-66 has good hydrophobicity and weather resistance. The use of UiO-66 to spray the surface of the super-strong fully delignified bamboo after densification treatment can effectively improve the weather resistance and waterproof performance of the bamboo board. So far, there has been no related research and reports. Summary of the invention

[0006] The purpose of the present invention is to provide a method for preparing a radiant cooling building enclosure material based on flattened bamboo boards in order to solve the problems that existing radiant cooling materials are difficult to recycle and naturally degrade.

[0007] The technical solution of the present invention is achieved in this way:

[0008] The present invention provides a method for preparing a radiant cooling building enclosure material based on flattened bamboo boards, comprising the following steps:

[0009] 1) placing the flattened bamboo board in a high-pressure reactor, adding alkali solution to remove the lignin component in the bamboo board to obtain a partially delignified bamboo board with a porous and fluffy cell wall structure, washing it to neutrality and then transferring it to a peracid solution to remove the residual lignin to obtain a white fully delignified bamboo board;

[0010] 2) subjecting the fully delignified bamboo board obtained in step 1) to mechanical compression treatment at room temperature to obtain a dense super-strong bamboo board;

[0011] 3) The ultra-strong bamboo board prepared in step 2) is subjected to surface spraying treatment using a UiO-66 solution, and after drying, a bamboo-based building enclosure material having radiant cooling performance and durability can be obtained.

[0012] As a further improvement of the present invention, the flattened bamboo board used in step 1) has a thickness of 2-10 mm, a width of 5-40 cm, and a length of 50-300 cm. The cellulose content of the flattened bamboo board is 30%-40%, the hemicellulose content is 20%-35%, the lignin content is 20%-35%, and the apparent density of the flattened bamboo board is 0.5-0.8 g / cm 3 .

[0013] As a further improvement of the present invention, the alkali solution described in step 1) is one or all of the following: sodium hydroxide, potassium hydroxide, sodium hydroxide and sodium sulfide, potassium hydroxide and sodium sulfide, sodium hydroxide and sodium sulfite, and a combination of potassium hydroxide and sodium sulfite, wherein the concentration of sodium hydroxide or potassium hydroxide is 1wt%-20wt%, and the concentration of sodium sulfide or sodium sulfite is 0.1wt%-10wt%; the solid-liquid ratio of the flattened bamboo board to the alkali solution is 1:5-1:20kg / L; the treatment temperature is 50-180°C, and the treatment time is 0.5-10h.

[0014] As a further improvement of the present invention, the peracid described in step 1) is one of performic acid, peracetic acid, persulfuric acid, peroxydisulfuric acid, and perbenzoic acid, or a mixed combination thereof, the concentration of the peracid is 15wt%-30wt%, the solid-liquid ratio of the flattened bamboo board to the peracid is 1:1-1:10kg / L, the treatment temperature is 25-80°C, and the treatment time is 0.5-48h.

[0015] As a further improvement of the present invention, when the alkali solution in step 1) removes lignin in the flattened bamboo board, the lignin removal rate is 40%-80%, and after the residual lignin is removed by peroxy acid, the lignin content in the white fully delignified bamboo board is not higher than 2%.

[0016] As a further improvement of the present invention, the temperature of the mechanical pressing in step 2) is 10-40° C., the pressure is 0.1-30 MPa, and the time is 0.5-24 h.

[0017] As a further improvement of the present invention, the density of the super-strong bamboo board in step 2) is 1.2-1.35 g / cm 3 ; Tensile strength is 600-1000MPa; Flexural strength is 240-400MPa.

[0018] As a further improvement of the present invention, the density of the super-strong bamboo board in step 2) is 1.2-1.35 g / cm 3 ; Tensile strength is 600-1000MPa; Flexural strength is 240-400MPa.

[0019] As a further improvement of the present invention, in step 3), UiO-66 is sprayed on the surface of the white bamboo board with a thickness of 0.1-2 mm.

[0020] The present invention further protects a radiant cooling building enclosure material based on flattened bamboo boards prepared by the above-mentioned preparation method.

[0021] The invention has the following beneficial effects: the invention uses alkali solution to partially remove lignin and hemicellulose in the bamboo board under high temperature and high pressure conditions, the hydroxide ions in the alkali solution break the ester bond and glycosidic bond in the lignin, a saponification reaction occurs, the lignin structure changes and dissolves in the solution, the cellulose swells, the cell wall becomes fluffy, and the hemicellulose is promoted to dissolve from the cell wall, so as to obtain a semi-delignified bamboo board with a porous and fluffy cell wall structure, and the lignin removal rate of the bamboo board is 40%-80%. The residual lignin is then oxidized and decomposed by a peroxy acid solution, and the residual lignin after the reaction is less than 2%. Due to the removal of lignin, hemicellulose and chromophore substances, the white fully delignified bamboo board has a large number of disordered micro-nano pores, an increased specific surface area, a large area of ​​air / solid interface, and the backscattering energy of cellulose strongly scatters sunlight to improve the reflectivity of the bamboo board. Secondly, the stretching vibration of chemical bonds such as COC and CO in the bamboo board gives the bamboo board a high emissivity in the 8-13μm band, which can radiate more energy to the atmosphere, thereby achieving a refrigeration effect. The mechanical strength of delignified bamboo boards will decrease. Cold pressing technology is used to press the porous and fluffy white bamboo boards into dense and super-strong bamboo boards, which can arrange the internal cellulose molecules more closely, and a large number of hydrogen bonds and van der Waals forces are formed between adjacent cellulose molecules, thereby improving the hardness, wear resistance, tensile strength and bending strength of the bamboo boards. Finally, the UiO-66 solid particles with excellent hydrophobicity and chemical stability are sprayed on the above bamboo boards to make new radiant cooling building enclosure materials with excellent mechanical properties, weather resistance and self-cleaning properties.

[0022] The building envelope material prepared by the present invention has the advantages of abundant raw materials and green environmental protection, and also has excellent mechanical properties and durability. When applied to building roofs or enclosures, it reduces the heat energy absorbed by the building through radiation energy, thereby reducing the energy consumption of the building. It is a new type of building envelope material with good application prospects.

[0023] The invention has a simple preparation process and low cost. The prepared new radiation cooling building enclosure material can be recycled or degraded, and is a green and environment-friendly radiation cooling material. BRIEF DESCRIPTION OF THE DRAWINGS

[0024] In order to more clearly illustrate the embodiments of the present invention or the technical solutions in the prior art, the drawings required for use in the embodiments or the description of the prior art will be briefly introduced below. Obviously, the drawings described below are only some embodiments of the present invention. For ordinary technicians in this field, other drawings can be obtained based on these drawings without paying creative labor.

[0025] Figure 1 The present invention is a flow chart of the preparation of the radiant cooling building enclosure material based on flattened bamboo boards;

[0026] Figure 2 The molecular structure formula of UiO-66 and the schematic diagram of the molecular structure of UiO-66 used in the present invention;

[0027] Figure 3 The UiO-66 solid powder and scanning electron microscope image used in the present invention;

[0028] Figure 4 This is the Fourier infrared spectrum of UiO-66 used in the present invention;

[0029] Figure 5 The actual pictures of bamboo materials in the process of being processed by the present invention, wherein a is the original flattened bamboo board; b is a partially delignified bamboo board with a porous and fluffy cell wall structure; c is a white fully delignified bamboo board;

[0030] Figure 6 Fourier transform infrared spectra of the original flattened bamboo board and the prepared partially delignified bamboo board and the white fully delignified bamboo board used in the present invention;

[0031] Figure 7 The actual pictures of the densely structured super-strong bamboo board and the coated UiO-66 super-strong bamboo board prepared by the present invention, wherein a is the densely structured super-strong bamboo board; b is the coated UiO-66 super-strong bamboo board;

[0032] Figure 8 XRD test graphs of UiO-66 used in the present invention, the prepared white fully delignified bamboo board, and the UiO-66 coated super-strong bamboo board;

[0033] Fig. 9 A tensile stress-strain curve diagram of the radiant cooling building enclosure material based on flattened bamboo panels prepared by the present invention;

[0034] Fig.10A simplified diagram of a temperature reduction test device for radiant cooling building envelope materials based on flattened bamboo panels prepared by the present invention;

[0035] Fig.11 The contact angles of the fully delignified bamboo board and the UiO-66 coated super-strong bamboo board prepared by the present invention with water droplets. DETAILED DESCRIPTION

[0036] The technical solutions in the embodiments of the present invention are described clearly and completely below. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of them. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0037] Example 1

[0038] Reference Figure 1 This embodiment provides a method for preparing a radiant cooling building enclosure material based on flattened bamboo boards, comprising the following steps:

[0039] (1) Prepare a sodium hydroxide solution with a mass fraction of 4 wt%. Add the unfolded bamboo board of 50 cm × 5 cm × 0.2 cm (length × width × thickness) and the alkali solution into a high-pressure reactor at a solid-liquid ratio of 1:5 kg / L, and react for 0.5 h at a reaction temperature of 50 ° C to obtain a partially delignified bamboo board with a porous and fluffy cell wall structure; after washing to neutrality, transfer to a 15 wt% peroxy acid solution, according to a solid-liquid ratio of 1:1 kg / L, react for 0.5 h at 25 ° C to completely remove the residual lignin, and obtain a white fully delignified bamboo board.

[0040] (2) placing the fully delignified bamboo board obtained in step 1) into a cold press molding machine, and mechanically pressing the board for 0.5 h at a pressure of 0.1 MPa and a temperature of 10° C. to obtain a dense super-strong bamboo board;

[0041] (3) Weighing 2 g of UiO-66 particle powder and dispersing it in 124 mL of ethanol to prepare a UiO-66 solution with a mass fraction of 2 wt%; Figure 2 The molecular structure formula and schematic diagram of the molecular structure of UiO-66 used in the present invention are as follows: Figure 2 As shown, the Zr6O4(OH)4 binding point coordinates with 12 terephthalic acid ligands to form a three-dimensional network structure and the Zr-O chemical bond is strong, so UiO-66 has the advantages of large specific surface area, high porosity, good thermal stability and weather resistance; Figure 3This is the UiO-66 used in the present invention and the scanning electron microscope image. From the image, it can be seen that the UiO-66 prepared in this specification is a white solid powder, the crystal size of which is at the nanometer level and has hydrophobic properties.

[0042] (4) Spray the UiO-66 solution prepared in step 3) on the dense super-strong bamboo board prepared in step 2) to a thickness of 0.1 mm. After drying, a bamboo-based building enclosure material with radiant cooling performance and durability can be obtained.

[0043] Example 2

[0044] Reference Figure 1 This embodiment provides a method for preparing a radiant cooling building enclosure material based on flattened bamboo boards, comprising the following steps:

[0045] (1) Prepare a sodium hydroxide solution with a mass fraction of 8 wt%. Add an unfolded bamboo board of 100 cm × 15 cm × 0.4 cm (length × width × thickness) and an alkali solution in a solid-liquid ratio of 1:10 kg / L into a high-pressure reactor, react at a reaction temperature of 80 ° C for 2 h, and obtain a partially delignified bamboo board with a porous and fluffy cell wall structure; after washing to neutrality, transfer to a 20 wt% peroxy acid solution, according to a solid-liquid ratio of 1:2.5 kg / L, react at 40 ° C for 4.5 h, completely remove the residual lignin, and obtain a white fully delignified bamboo board.

[0046] (2) placing the fully delignified bamboo board obtained in step 1) into a cold press molding machine, and mechanically pressing the board for 0.5 h at a pressure of 6 MPa and a temperature of 10° C. to obtain a dense super-strong bamboo board;

[0047] (3) Weigh 4 g of UiO-66 granular powder and disperse it in 122 mL of ethanol to prepare a UiO-66 solution with a mass fraction of 4 wt%;

[0048] (4) Spray the UiO-66 solution prepared in step 3) on the dense super-strong bamboo board prepared in step 2) to a thickness of 0.8 mm. After drying, a bamboo-based building enclosure material with radiant cooling performance and durability can be obtained.

[0049] Example 3

[0050] Reference Figure 1 This embodiment provides a method for preparing a radiant cooling building enclosure material based on flattened bamboo boards, comprising the following steps:

[0051] (1) Prepare a sodium hydroxide solution with a mass fraction of 12 wt%. Add the unfolded bamboo board of 150 cm × 25 cm × 0.6 cm (length × width × thickness) and the alkali solution into a high-pressure reactor at a solid-liquid ratio of 1:15 kg / L, and react for 4.5 h at a reaction temperature of 120 ° C to obtain a partially delignified bamboo board with a porous and fluffy cell wall structure; after washing to neutrality, transfer to a 25 wt% peroxy acid solution, according to a solid-liquid ratio of 1:5 kg / L, react at 55 ° C for 8.5 h, completely remove the residual lignin, and obtain a white fully delignified bamboo board.

[0052] (2) placing the fully delignified bamboo board obtained in step 1) into a cold press molding machine, and mechanically pressing the board for 8 hours at a pressure of 12 MPa and a temperature of 30° C. to obtain a dense super-strong bamboo board;

[0053] (3) Weigh 6 g of UiO-66 particle powder and disperse it in 119 mL of ethanol to prepare a UiO-66 solution with a mass fraction of 6 wt%;

[0054] (4) Spray the UiO-66 solution prepared in step 3) on the dense super-strong bamboo board prepared in step 2) to a thickness of 1.2 mm. After drying, a bamboo-based building enclosure material with radiant cooling performance and durability can be obtained.

[0055] Example 4

[0056] Reference Figure 1 This embodiment provides a method for preparing a radiant cooling building enclosure material based on flattened bamboo boards, comprising the following steps:

[0057] (1) Prepare a sodium hydroxide solution with a mass fraction of 16 wt%. Add an unfolded bamboo board of 200 cm × 35 cm × 0.8 cm (length × width × thickness) and an alkali solution in a solid-liquid ratio of 1:20 kg / L into a high-pressure reactor, react at a reaction temperature of 140 ° C for 7 h, and obtain a partially delignified bamboo board with a porous and fluffy cell wall structure; after washing to neutrality, transfer to a 30 wt% peroxy acid solution, according to a solid-liquid ratio of 1:7.5 kg / L, react at 80 ° C for 12.5 h to remove residual lignin, and obtain a white fully delignified bamboo board.

[0058] (2) placing the fully delignified bamboo board obtained in step 1) into a cold press molding machine, and mechanically pressing for 16 hours at a pressure of 24 MPa and a temperature of 40° C. to obtain a dense super-strong bamboo board;

[0059] (3) Weigh 8 g of UiO-66 granular powder and disperse it in 117 mL of ethanol to prepare a UiO-66 solution with a mass fraction of 8 wt%;

[0060] (4) Spray the UiO-66 solution prepared in step 3) on the dense super-strong bamboo board prepared in step 2) to a thickness of 1.6 mm. After drying, a bamboo-based building enclosure material with radiant cooling performance and durability can be obtained.

[0061] Example 5

[0062] Reference Figure 1 This embodiment provides a method for preparing a radiant cooling building enclosure material based on flattened bamboo boards, comprising the following steps:

[0063] (1) Prepare a sodium hydroxide solution with a mass fraction of 20 wt%. Add an unfolded bamboo board of 300 cm × 40 cm × 1 cm (length × width × thickness) and an alkali solution in a solid-liquid ratio of 1:20 kg / L into a high-pressure reactor, react at a reaction temperature of 180 ° C for 10 h, and obtain a partially delignified bamboo board with a porous and fluffy cell wall structure; after washing to neutrality, transfer to a 30 wt% peroxy acid solution, according to a solid-liquid ratio of 1:10 kg / L, react at 80 ° C for 48 h to remove the residual lignin, and obtain a white fully delignified bamboo board.

[0064] (2) placing the fully delignified bamboo board obtained in step 1) into a cold press molding machine, and mechanically pressing the board for 24 hours at a pressure of 30 MPa and a temperature of 30° C. to obtain a dense super-strong bamboo board;

[0065] (3) Weighing 10 g of UiO-66 particle powder and dispersing it in 114 mL of ethanol to prepare a UiO-66 solution with a mass fraction of 10 wt%;

[0066] (4) Spray the UiO-66 solution prepared in step 3) on the dense super-strong bamboo board prepared in step 2) to a thickness of 2.0 mm. After drying, a bamboo-based building enclosure material with radiant cooling performance and durability can be obtained.

[0067] Comparative Example 1

[0068] The difference from Example 4 is that in step 1), alkali solution is not used to quickly delignify the bamboo under high temperature and high pressure conditions. The other steps and parameters are the same as those in Example 4.

[0069] (1) A bamboo board of 200 cm × 35 cm × 0.8 cm (length × width × thickness) was immersed in a 30 wt% peracid solution at a solid-liquid ratio of 1:7.5 kg / L and reacted at 80° C. for 12.5 h to remove lignin and obtain a delignified bamboo board.

[0070] (2) placing the delignified bamboo board in step 1) into a cold press molding machine, and mechanically pressing the board for 16 hours at a pressure of 9 MPa and a temperature of 40° C. to obtain a dense super-strong bamboo board;

[0071] (3) Weigh 8 g of UiO-66 granular powder and disperse it in 117 mL of ethanol solvent to prepare a UiO-66 solution with a mass fraction of 8 wt%;

[0072] (4) Spray the UiO-66 solution prepared in step 3) on the dense super-strong bamboo board prepared in step 2) to a thickness of 1.6 mm. After drying, a bamboo-based building enclosure material with radiant cooling performance and durability can be obtained.

[0073] Comparative Example 2

[0074] The difference from Example 4 is that no peracid solution is added in step 2), and the other steps and parameters are the same as those in Example 4.

[0075] (1) A sodium hydroxide solution with a mass fraction of 16 wt% was prepared. A bamboo board of 200 cm×35 cm×0.8 cm (length×width×thickness) and an alkali solution were added into a high-pressure reactor at a solid-liquid ratio of 1:20 kg / L, and the reaction was carried out at a reaction temperature of 140°C for 7 h to obtain a partially delignified bamboo board with a porous and fluffy cell wall structure;

[0076] (2) placing the bamboo board in step 1) into a cold press molding machine and mechanically pressing the bamboo board for 16 hours at a pressure of 9 MPa and a temperature of 40° C. to obtain a densely structured super-strong bamboo board;

[0077] (3) Weigh 8 g of UiO-66 granular powder and disperse it in 117 mL of ethanol solvent to prepare a UiO-66 solution with a mass fraction of 8 wt%;

[0078] (4) Spraying the UiO-66 solution prepared in step 3) on the dense super-strong bamboo board prepared in step 2) with a spraying thickness of 1.6 mm. After drying, a bamboo-based building enclosure material with radiant cooling performance and durability can be obtained.

[0079] Comparative Example 3

[0080] The difference from Example 4 is that in step 4), the UiO-66 solution is not sprayed, and the other steps and parameters are the same as those in Example 4.

[0081] (1) Prepare a sodium hydroxide solution with a mass fraction of 16 wt%. A bamboo board of 200 cm × 35 cm × 0.8 cm (length × width × thickness) and an alkali solution are added to a high-pressure reactor at a solid-liquid ratio of 1:20 kg / L, and reacted at a reaction temperature of 140 ° C for 7 hours. A semi-delignified bamboo board with a porous and fluffy cell wall structure is obtained; after washing and soaking until neutral, it is transferred to a 30 wt% peroxy acid solution, and reacted at 80 ° C for 12.5 hours according to a solid-liquid ratio of 1:7.5 kg / L to remove residual lignin and hemicellulose, and obtain a white fully delignified bamboo board.

[0082] (2) The white fully delignified bamboo board prepared in step 1) is placed in a cold press molding machine and mechanically pressed for 16 hours at a pressure of 9 MPa and a temperature of 40° C. to obtain a dense super-strong bamboo board.

[0083] The following tests were performed on the radiant cooling building envelope material based on flattened bamboo panels prepared in this embodiment:

[0084] Test Example 1

[0085] Scanning electron microscopy was used to analyze UiO-66. Figure 3 .Depend on Figure 3 It can be seen that the crystal size of the UiO-66 sample is about 8-10nm, with a large specific surface area, no obvious flocculation, and good dispersion, which is conducive to subsequent coating applications.

[0086] Test Example 2

[0087] Fourier transform infrared spectrometer was used to analyze the UiO-66, flattened bamboo board, partially delignified bamboo board and white fully delignified bamboo board (see the figure below). Figure 5 ) to characterize and analyze the special peaks of chemical bonds. The test range is set to 400-4000cm -1 ,get Figure 4 and Figure 6 .

[0088] The results of infrared spectroscopy test and analysis show that the lignin and hemicellulose of the bamboo board treated with alkali and peroxyacid have been completely removed, and the strong absorption peaks of COC and CO chemical bonds in the cellulose of the bamboo board are at 1164cm -1 and 1039cm -1 Nearby, in the 8-13μm band range, the bamboo board has excellent emissivity in the atmospheric window band, and can radiate most of the energy into outer space to achieve cooling performance.

[0089] Test Example 3

[0090] X-ray powder diffractometer was used to test UiO-66, white delignified bamboo board and coated UiO-66 super strong bamboo board (actual picture as shown in the figure) Figure 7 ), the test condition is Cu-Kα radiation source The tube voltage was 40 kV, the current was 40 mA, the scanning rate was 2 ° / min, and the scanning range was 2θ = 5-50 °. Figure 8 .like Figure 8 As shown, UiO-66 has been successfully coated onto the dense and ultra-strong bamboo board.

[0091] Test Example 4

[0092] The radiant cooling building envelope materials based on flattened bamboo boards prepared in Examples 1-5 of the present invention and Comparative Examples 1-3 were tested and analyzed for chemical components, and the experimental data are shown in Table 1.

[0093] Table 1 Chemical component contents of the new radiant cooling building enclosure material based on flattened bamboo boards prepared in Examples 1-5 and Comparative Examples 1-3

[0094]

[0095]

[0096] As shown in Table 1, the residual lignin in the bamboo board treated with alkali solution and peroxy acid solution is less than 2%, which is comparable to Figure 6 Correspondingly, due to the reduction of a large number of light-absorbing substances and color groups, the white fully delignified bamboo board can significantly reduce the absorption of sunlight, which is conducive to the realization of radiant cooling.

[0097] Test Example 5

[0098] The bending properties of the radiant cooling building envelope materials based on flattened bamboo boards prepared in Examples 1-5 and Comparative Examples 1-3 of the present invention were tested using a universal mechanical testing machine, and the data were collated to prepare Table 2.

[0099] The stress-strain performance of the radiant cooling building enclosure materials based on flattened bamboo boards prepared in Examples 1-5 and Comparative Examples 1-3 of the present invention was tested using a universal mechanical testing machine, and the data obtained were shown in Table 2. Fig. 9 .

[0100] Table 2 Bending strength and bending modulus of the new radiant cooling building enclosure material based on flattened bamboo board prepared in Examples 1-5 and Comparative Examples 1-3

[0101]

[0102]

[0103] From Table 2 and Fig. 9 It can be seen that the radiant cooling building envelope materials based on flattened bamboo boards prepared in Examples 1-5 of the present invention have good bending strength. The bending strength of the bamboo board after cold pressing is increased from 210 MPa to 400 MPa, and the tensile strength is also significantly improved, indicating that the new radiant cooling building envelope material has excellent mechanical properties.

[0104] Test Example 6

[0105] (1) An outdoor cooling test was performed on the radiant cooling building envelope materials based on flattened bamboo panels prepared in Examples 1-5 and Comparative Examples 1-3. Fig.10 The following are simplified and actual pictures of the test device. The test chamber is a polystyrene foam box (25cm×25cm×5cm) with an open top. The outside of the box is wrapped with aluminum foil, and a polyethylene film (30μm thick) is used as a windshield to cover the top of the box, mainly to reduce heat conduction and convection between the sample and the environment. The surface of the sample to be tested is 1cm away from the top film. K-type thermocouples (accuracy of ±0.5℃) are placed at the center of the back of the sample to be tested and outside the box and connected to a data recorder. A set of data is recorded every hour to determine the temperature changes of the sample and the environment as shown in Table 3 and the maximum temperature difference during the day (ΔT max ) as shown in Table 4.

[0106] (2) The emissivity of the flattened bamboo board-based radiant cooling building enclosure materials prepared in Examples 1-5 and Comparative Examples 1-3 was tested in the sunlight band (0.3-2.5 μm) using an ultraviolet-visible-near-infrared spectrophotometer equipped with an integrating sphere. Specifically, the reflectivity in the visible light band (R solar ) as shown in Table 4.

[0107] (3) The emissivity of the radiative cooling building envelope materials based on flattened bamboo boards prepared in Examples 1-5 and Comparative Examples 1-3 was tested in the mid-infrared band (2.5-25 μm) using a Fourier transform infrared spectrometer equipped with an integrating sphere accessory. IR ) as shown in Table 4.

[0108] Table 3 Temperature change record of the new radiant cooling building enclosure material based on flattened bamboo board and the environment prepared in Example 4

[0109]

[0110]

[0111] Table 4 R of the new radiant cooling building enclosure material based on flattened bamboo board prepared in Examples 1-5 and Comparative Examples 1-3 solar ,∈ IR , ΔT maxStatistics table

[0112] sample <![CDATA[R solar / (%)]]> <![CDATA[∈ IR / (%)]]> <![CDATA[ΔT max / (℃)]]> Example 1 91.7 86.8 8.6 Example 2 92.3 88.5 8.7 Example 3 92.9 89.7 9.0 Example 4 95.4 91.8 9.5 Example 5 94.6 90.2 9.2 Comparative Example 1 90.5 83.9 3.6 Comparative Example 2 91.2 85.4 3.1 Comparative Example 3 88.4 89.5 3.2

[0113] As shown in Table 4, the cooling temperature of Comparative Examples 1-3 is not as good as that of Example 4. This is mainly because the lignin removal rate in the flattened bamboo board-based radiation cooling building enclosure materials prepared in Comparative Examples 1 and 2 is low. On the one hand, fewer microporous cavities are formed, and the performance of reflecting sunlight is reduced. On the other hand, the residual lignin will absorb part of the solar radiation and reduce the cooling effect. However, the poor cooling performance of Comparative Example 3 is because there is no spraying of UiO-66 solution, no scattering effect of UiO-66 white particles, and the reflectivity of the radiation cooling building enclosure new material is reduced, resulting in the radiation cooling performance of Comparative Example 3 being lower than that of Example 4.

[0114] According to Table 4, the radiative cooling building envelope materials based on flattened bamboo boards prepared in Examples 1-5 of the present invention have a reflectivity of 91-96% in the spectral range of 0.3-2.5 μm, and an emissivity of 87-92% in the atmospheric window band.

[0115] From Tables 3 and 4, it can be seen that the radiant cooling building envelope material based on flattened bamboo boards can be 9.5°C lower than the ambient temperature during the day, achieving a daytime cooling effect. If this material is applied to the construction industry, it can effectively reduce the power consumption of air conditioning and has good development prospects.

[0116] Test Example 7:

[0117] 4 μL of water was dropped on the surface of the fully delignified bamboo board and the UiO-66 coated super-strong bamboo board. The contact angle of water was measured using a contact angle meter at room temperature. The contact angles at 5 different positions were taken for each sample, and the average value was taken as the measurement result. Fig.11 As shown in the figure, the contact angle between the fully delignified bamboo board and the water droplet is 12.3°, and the contact angle between the UiO-66 coated super-strong bamboo board and the water droplet is 81°. Therefore, coating UiO-66 is beneficial to improving the hydrophobic properties of radiant cooling building envelope materials based on flattened bamboo boards.

[0118] The preparation method used in the invention is simple, the production cost is low, and the bamboo board used can be recycled or degraded, which is environmentally friendly.

[0119] The above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. Any modifications, equivalent substitutions, improvements, etc. made within the spirit and principles of the present invention should be included in the protection scope of the present invention.

Claims

1. A method for preparing a radiant cooling building enclosure material based on flattened bamboo boards, characterized in that: The following steps are involved: 1) placing the flattened bamboo board in a high-pressure reactor, adding alkali solution to remove the lignin component in the bamboo board to obtain a partially delignified bamboo board with a porous and fluffy cell wall structure, washing it to neutrality and then transferring it to a peracid solution to remove the residual lignin to obtain a white fully delignified bamboo board; 2) subjecting the fully delignified bamboo board obtained in step 1) to mechanical compression treatment at room temperature to obtain a dense super-strong bamboo board; 3) The ultra-strong bamboo board prepared in step 2) is subjected to surface spraying treatment using a UiO-66 solution, and after drying, a bamboo-based building enclosure material having radiant cooling performance and durability can be obtained.

2. The preparation method according to claim 1, characterized in that: The flattened bamboo board used in step 1) has a thickness of 2-10 mm, a width of 5-40 cm, and a length of 50-300 cm. The cellulose content of the flattened bamboo board is 30%-40%, the hemicellulose content is 20%-35%, the lignin content is 20%-35%, and the apparent density of the flattened bamboo board is 0.5-0.8 g / cm 3 .

3. The preparation method according to claim 1, characterized in that: The alkali solution described in step 1) is one or all of sodium hydroxide, potassium hydroxide, sodium hydroxide and sodium sulfide, potassium hydroxide and sodium sulfide, sodium hydroxide and sodium sulfite, and a combination of potassium hydroxide and sodium sulfite, wherein the concentration of sodium hydroxide or potassium hydroxide is 1wt%-20wt%, and the concentration of sodium sulfide or sodium sulfite is 0.1wt%-10wt%; the solid-liquid ratio of the flattened bamboo board to the alkali solution is 1:5-1:20kg / L; the treatment temperature is 50-180°C, and the treatment time is 0.5-10h.

4. The preparation method according to claim 1, characterized in that: The peracid described in step 1) is one of performic acid, peracetic acid, persulfuric acid, peroxydisulfuric acid, and perbenzoic acid, or a mixed combination thereof; the concentration of the peracid is 15wt%-30wt%, the solid-liquid ratio of the flattened bamboo board to the peracid is 1:1-1:10kg / L, the treatment temperature is 25-80°C, and the treatment time is 0.5-48h.

5. The preparation method according to claim 1, characterized in that: Step 1) When the alkali solution is used to remove lignin in the flattened bamboo board, the lignin removal rate is 40%-80%. After the residual lignin is removed by peroxy acid, the lignin content in the white fully delignified bamboo board is not higher than 2%.

6. The preparation method according to claim 1, characterized in that: The temperature of the mechanical pressing in step 2) is 10-40°C, the pressure is 0.1-30MPa, and the time is 0.5-24h.

7. The preparation method according to claim 1, characterized in that: Step 2) The density of the super strong bamboo board is 1.2-1.35 g / cm 3 ; Tensile strength is 600-1000MPa; Flexural strength is 240-400MPa.

8. The preparation method according to claim 1, characterized in that: The UiO-66 solution described in step 3) is prepared by dispersing 1-10 g of UiO-66 particle powder into 114 mL-125 mL of ethanol, that is, preparing a UiO-66 solution with a mass fraction of 1 wt%-10 wt%.

9. The preparation method according to claim 1, characterized in that: Step 3) UiO-66 is sprayed on the surface of the white bamboo board with a thickness of 0.1-2mm.

10. A radiant cooling building envelope material based on flattened bamboo boards prepared by the preparation method according to any one of claims 1 to 9.